1993
DOI: 10.1159/000267326
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Interplexif orm Cells in the Retina of Pigmented and Hypopigmented Quails (Coturnix coturnix japonica)

Abstract: Interplexiform cells (IPCs) have not been previously described as a component of the population of tyrosine hydroxylase (TH) immunoreactive (presumably dopaminergic) cells in the avian retina. In this study, carried out in both pigmented and imperfect albino mutant quails (Coturnix coturnix japonica), we initially describe TH immunoreactive cells in the inner nuclear layer whose internal dendritic arborization extends into strata 1 3 and 4/5 of the inner plexiform layer. Then, we describe ascending processes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Interplexiform cells are a particular type of amacrine cell projecting to both plexiform layers (Dowling and Ehinger, 1975). These cells have been described as dopaminergic in the retinae of lampreys (Dalil‐Thiney et al, 1996), fishes (Van Haesendonck et al, 1993), amphibians (Vigh et al, 2000), lizards (Lanuza et al, 1996), birds (Dkhissi et al, 1993), and mammals (Gustincich et al, 1999). They interconnect the inner and outer plexiform layers (Djamgoz and Wagner, 1992) and possess GABA receptors (Gustincich et al, 1999), a finding indicating that they may act under GABA modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interplexiform cells are a particular type of amacrine cell projecting to both plexiform layers (Dowling and Ehinger, 1975). These cells have been described as dopaminergic in the retinae of lampreys (Dalil‐Thiney et al, 1996), fishes (Van Haesendonck et al, 1993), amphibians (Vigh et al, 2000), lizards (Lanuza et al, 1996), birds (Dkhissi et al, 1993), and mammals (Gustincich et al, 1999). They interconnect the inner and outer plexiform layers (Djamgoz and Wagner, 1992) and possess GABA receptors (Gustincich et al, 1999), a finding indicating that they may act under GABA modulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the variability in the retinal cellular type immunostained for TH may be related to differences in adaptation to particular lifestyles rather than phylogenetic relationships (Dkhissi et al 1993;Lanuza et al 1996).…”
Section: Retinamentioning
confidence: 99%